Kajian Pengelolaan Instalasi Pengolahan Air Limbah di Rumah Sakit - Difana Meilani; Mohammad Hanif (Dampak, 2019)
Risk management is a process of knowing, analyzing, and controlling risks of every activity in product and, service sectors. The aims are the process runs effectively and efficiently. One of the ISO studies on risk management has been guided in ISO 31000. This ISO provides a standard framework with the title "Risk Management-Principles and Guidelines on Implementation". Based on the sources in the Ministry of Health in 2016, there are 2,488 hospitals spread throughout Indonesia. However, only 10.29% of hospitals have ability to control the Wastewater Treatment Plant (WWTP) properly. The purposes of this research are determining risk priority of Wastewater Treatment Installation and prioritizing risk evaluation of WWTP at Ibnu Sina hospital, Padang. In this research, fuzzy AHP method was used. The questionnaire was validated by environmental department which monitors hospitals’ waste. After ranking the priority risk, Risk Breakdown Structure method was then being used to evaluate the risk that has potentiallty in waste water processing.The result from the fuzzy AHP are five risks, the main priority risk is the pipe with sub risk of liquid waste stuck with value of 0,0779. The second risk is septictank with excess nitrification sub risk with value of 0,0713. The third risk is the sampit with subcritical liquid waste spilled with value of 0,0642. The fourth risk is the lack quality of human resources with the weight value of 0,0590 and the fifth risk is the blower with the condition is not feasible to use with the weight value of 0,0548.